Belief Shift or Only Facilitation: How Semantic Expectancy Affects Processing of Speech Degraded by Background Noise - Simeon, Katherine M.; Bicknell, Klinton; Grieco-Calub, Tina M. (Frontiers in Psychology, 2018)
Individuals use semantic expectancy – applying conceptual and linguistic knowledge to speech input – to improve the accuracy and speed of language comprehension. This study tested how adults use semantic expectancy in quiet and in the presence of speech-shaped broadband noise at -7 dB and -12 dB signal-to-noise ratio (SNR). Twenty-four adults (22.1 ± 3.6 years, mean ± SD) were tested on a four-alternative-forced-choice task whereby they listened to sentences and were instructed to select an image matching the sentence-final word. The semantic expectancy of the sentences was unrelated to (neutral), congruent with, or conflicting with the acoustic target. Congruent expectancy improved accuracy and conflicting expectancy decreased accuracy relative to neutral, consistent with a theory where expectancy shifts beliefs toward likely words and away from unlikely words. Additionally, there were no significant interactions of expectancy and noise level when analyzed in log-odds, supporting the predictions of ideal observer models of speech perception.